Risk of death due to chronic chagasic cardiopathy - Enrique C Manzullo; Roberto Chuit (Memorias do Instituto Oswaldo Cruz, 1999)
In this longitudinal study 5,710 people were included. The inclusion criteria were two positive serological results for Trypanosoma cruzi infection, 15 and 50 years old and no other demostrable diesease at the time of study. In the five year follow up 1,117 patients were lost. The follow up involved yearly evaluation of serology, clinical examination, X-ray of torax, and ECG, for 4,593 patients and 263 were contacted at home because they did not assist for their clinical consultant. Time average of follow up was 5.3 years. Eighty nine (1.5%) of the 4,593 patients died during the follow-up period, 63 (71%) by cardiac insufiency (CI) and 26 (29%) by severe ventricular arrithmias. Diagnosis of cardiomegaly was present in all the patients with diagnosis of CI and in 15 (5%) of the patients with diagnosis of arrithmias.The ECG alterations of these pacients show 61 right bundle brunch block (RBBB), associated or not with left anterior hemiblock (LAHB), 47 pathological Q wave and 70 primary repolarization alterations; 61 had polyfocal ventricular arrithmia. The death rate was similar in the sexes and was more frequent between 40 and 50 years of age. Information on 1,380 recuperated patients shows that 15 died with no previous symptoms and without medical assistance and were interpretate as sudden death. The latest ECG in three follow-up of these pacients indicates (before death) that only one had normal study and 14 presented 12 RBBB; 9 LAHB; 7 isolated ventricular arrithmia; 10 repolariz alterations; 2 patological Q wave, 10 patients of them with RBBB and repolariz alterations. In all the cases we had people between 35 and 43 years old, 9 men and 6 women. This study shows that in Chagas disease is possible to differenciate two risk groups. A low risk death group that have normal ECG and clinical evaluation during the follow up, and a high risk group associate ECG with RBBB and primary alterations of repolarization and/or inactivation zones with not anual clinical evaluation.